Ягге и магия вуду: повесть / Дмитрий Емец - Емец Дмитрий Александрович (Серия "Любимые книги Тани Гроттер", 2006)
Экземпляры: (20200220) / Инвентарный номер: 31559 / Цена: 92.60 / Сис.шифр: Р2 / Авт.знак: Е 60 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6